The gliding phase in swimming: The effect of water depth - Marinho, D. A.; Barbosa, T. M.; Mantripragada, N.; Vilas-Boas, J. P.; Rouard, A. H.; Mantha, V.; Rouboa, A. I.; Silva, A. J. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Aiming to achieve higher performances, swimmers should maximize each component of swimming races. During starts and turns, the gliding phase represents a determinant part of these race components. Thus, the depth position allowing minimizing the hydrodynamic drag force represents an important concern in swimming research. The aim of this study was to analyse the effect of depth on drag during the underwater gliding, using computational fluid dynamics (CFD) METHODS: The 3-D domain representing part of a swimming pool was 3.0 m depth, 3.0 m width and 11.0 m length. CFD simulations were applied to the flow around a 3-D model of a male adult swimmer in a prone gliding position with the arms extended at the front (Marinho et al., 2009). General moving object model was used to model the body as the moving object. During the gliding, the swimmer model`s middle line was placed at different water depths: 0.20m (just under the surface), 0.50 m, 1.0 m, 1.50 m (middle of the pool), 2.0m, 2.50m and 2.80m (bottom of the pool). The coefficient of drag and the hydrodynamic drag force were computed using a steady flow velocity of 1.60m/s for the different depths run for 3 seconds in each case. RESULTS: The coefficient of drag was 0.67, 0.62, 0.53, 0.44, 0.36, 0.30, 0.28 and the drag force was 100.20 N, 92.30 N, 80.50 N, 65.40 N, 53.40 N, 44.70 N and 42.0 N when gliding at a water depth of 0.20 m, 0.50 m, 1.0 m, 1.50 m, 2.0 m, 2.50 m and 2.80 m, respectively, at the time of 2 seconds when the swimmer was approximately at the middle of the computational pool. DISCUSSION: The water depth seems to have a positive effect on reducing hydrodynamic drag during the gliding. Moreover, gliding near the bottom of the pool also presented lower drag values compared to gliding at a water depth, for instance, in the middle of the swimming pool. This finding could suggest that the positive effects of water depth are more powerful than the possible negative hydrodynamic effects of turbulence near the bottom of the pool, expected when the simulations are not carried-out with a moving model. Reducing the drag experienced by swimmers during the glide off the wall can enhance start and turn performances. Therefore, a commitment between decreasing drag (by increasing water depth) and gliding travel distance should be a main concern of swimmers and an important goal to be studied in future investigations.